Development of the simulation model for throwing motion in water polo - Nakashima, M.; Nakayama, Y.; Minami, Y.; Takagi, H. (Sports Engineering, 2014)
The simulation model for the throwing motion in water polo was developed. The input data for the simulation, such as the joint motion and body geometry of the thrower, were acquired in the experiment in which a subject player threw a ball. The simulation reproducing the experiment and the simulation without fluid forces were conducted. From the simulation reproducing the experiment, it was found that the discrepancies between the simulated and experimental displacements were found to be 4 % for the middle point of the waist and 7 % for the wrist of the throwing hand. The simulated initial ball velocity was found to be 19.2 m/s, which was close to the value of 20 m/s reported in the previous studies. From the simulation without fluid forces, 38 % reduction in the initial ball velocity was found.